Getting Back on Track with Turkey - Daniel S. Hamilton (Intereconomics, 2018)
European countries and the United States face a delicate set of challenges in dealing with Turkey. Most have long-standing relationships with Ankara and important interests at stake in the country's future. Yet the arrangements that have historically anchored each of their strategically important ties - the prospect of Turkey's eventual EU accession and its decades-long military alliance with the United States and other NATO members - are being challenged by divisions within Turkish society and government actions that have raised questions about Turkey's role within Western structures.
Keywords: 330; Crisis management; South Eastern Europe; Trade policy; Turkey